Validation of VANET message dissemination algorithms otherwise vulnerable to broadcast storms in urban contexts. Issue 10 (19th May 2021) - AlQahtani, Osama; Sheldon, Frederick T.
Abstract: Warning messages in vehicular ad‐hoc networks have strict delay requirements (ie, hard real‐time deadlines) since they are meant to prevent accidents. However, reliable dissemination methods using the common dedicated short‐range communication (DSRC) interface such as pure broadcasting at each vehicle suffer because they are vulnerable to overwhelming the radio channel in high traffic urban contexts where signal propagation is obstructed. This is a well‐known problem called a broadcast storm. This problem can be alleviated by clustering vehicles and coordinating their communications via Cluster Masters—reduced percentages of informed vehicles, especially in urban scenarios, where there are frequent obstacles to the DSRC channels. Therefore, in addition to clustering, this work proposes a novel combination of Cluster Forwarders, that are vehicles elected to help in transmitting messages around obstacles, and fifth generation mobile network as the vehicle‐to‐infrastructure technology to increase the reach of the disseminated messages. New protocols featuring this combination are proposed to tackle broadcast storms focusing on keeping the percentage of informed vehicles as high as possible. Simulation results are presented to show how these new protocols outperform the benchmark ones in terms of percentage of informed vehicles and of dissemination delays. Abstract : The combination of clustering, Cluster Forwarder vehicles, and fifth generation mobile network on vehicular ad‐hoc network communications are used with different communication chains, allowing us to find the highest percentages of informed vehicles and lowest delays to inform the last vehicle in the network.